2018
DOI: 10.1136/tobaccocontrol-2018-054491
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effect of a potential policy to restrict tobacco retail availability in New Zealand

Abstract: A tobacco retail reduction policy that prevented new retail outlets from selling tobacco and grandfathered existing retailers would be unlikely to achieve New Zealand's target of a 95% reduction in tobacco outlet density within several decades of being enacted. Nonetheless, this policy could achieve a 50% reduction in tobacco retail availability in the first decade of implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The strengths in this paper lie in evaluating the density reduction and equity of a range of potential policies. Previous studies have evaluated a single or small number of policies [17][18][19]21,22], and few have evaluated the equity impact [21,22]. We explicitly evaluated density reduction and equity-impact of twelve potential policies selected based on previous research, many of which have been considered elsewhere [19,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strengths in this paper lie in evaluating the density reduction and equity of a range of potential policies. Previous studies have evaluated a single or small number of policies [17][18][19]21,22], and few have evaluated the equity impact [21,22]. We explicitly evaluated density reduction and equity-impact of twelve potential policies selected based on previous research, many of which have been considered elsewhere [19,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Potential policy solutions to reduce TOD across neighbourhoods include restricting the types of businesses that can sell tobacco, such as only liquor stores, and regulating where tobacco retailers can locate, such as exclusion zones around schools [16]. Some studies have quantified the impact of such policies on overall TOD [17,18], or the cost of tobacco products [19,20]. Few studies have explicitly focused on the equity-impact of prospective policy interventions to control tobacco availability, but those that have showed that the equityimpacts of different policy options vary widely [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Finding an optimal non-regulatory intervention to complement strong tobacco control policies and laws requires further research. A future intervention may be most effective if there is a ban on new tobacco retailers,10 11 or in the context of a jurisdiction, such as San Francisco, where there is a cap on the number of tobacco retailers permitted, but existing tobacco retailers are ‘grandfathered’-in and allowed to continue to sell until they end sales naturally (eg, business closure) 10…”
Section: Discussionmentioning
confidence: 99%
“…Although tobacco control stakeholders suggest that measures to reduce the retail availability of tobacco may hold promise, few interventions have been evaluated and published. Governments have been encouraged to use laws and policies (regulatory interventions), such as banning new tobacco retailers, or requiring a retailer to hold a tobacco licence, as a mechanism to reduce the density and number of tobacco retailers 10 11. Previous Australian research has shown that a large licence fee increase alone can reduce the number of tobacco retailers 12…”
Section: Introductionmentioning
confidence: 99%
“…There is now evidence (largely from countries advanced in reducing smoking) that outlet density and the location of tobacco retailers affects youth smoking and adult quit rates 4 6–8. Studies examining alternatives to current models of tobacco and nicotine supply have identified the need to drastically reduce tobacco outlets, and called for limits on the types of outlet permitted to sell tobacco 9–12. Given the need for regulating tobacco sources and the difficulties involved,13 14 what should the ultimate goals be regarding the supply of tobacco and non-prescription nicotine products?…”
Section: Introductionmentioning
confidence: 99%